Case report: Focal segmental glomerulosclerosis and nephrotic syndrome following treatment with pamidronate for calcitriol toxicity - Dawson, Katherine Ann; Blong, April; Walton, Rebecca (Frontiers in Veterinary Science, 2022)
Objective This study aimed to describe a case of glomerulosclerosis resulting in nephrotic syndrome following the administration of pamidronate disodium to treat clinical calcitriol toxicity in a dog. Case summary A 12-week-old intact male Labrador Retriever weighing 11.8 kg presented with lethargy and vomiting for 20 h after ingesting a 100 g tube of topical antipsoriatic cream (3 mcg/g of calcitriol; Vectical Ointment™, Galderma, Lausanne, Switzerland). Severe hypercalcemia was present on the day of the presentation. Hypercalcemia treatments such as saline diuresis, furosemide (Salix®, furosemide, Merck Animal Health, Kenilworth, NJ), and dexamethasone sodium phosphate (Dexamethasone SP, Mylan, Canonsburg, PA) were initiated. The dog was also administered a single dose of pamidronate disodium (Pamidronate disodium, Mylan, Canonsburg, PA) on the day of presentation. Initially, the patient's clinical signs improved, and the hypercalcemia resolved. Exactly 130 h post-pamidronate disodium (Dexamethasone SP, Mylan, Canonsburg, PA) administration, the patient developed biochemical abnormalities and severe edema, consistent with nephrotic syndrome, and was euthanized. Necropsy results revealed evidence of focal segmental glomerulosclerosis (FSGS). Unique information Pamidronate disodium, commonly used for the treatment of hypercalcemia, may have resulted in glomerulosclerosis and nephrotic syndrome in a dog with calcitriol toxicity. This complication should be taken into consideration when monitoring patients treated with pamidronate disodium for hypercalcemia.